2014
DOI: 10.1186/1754-6834-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Close relationship of a novel Flavobacteriaceaeα-amylase with archaeal α-amylases and good potentials for industrial applications

Abstract: BackgroundBioethanol production from various starchy materials has received much attention in recent years. α-Amylases are key enzymes in the bioconversion process of starchy biomass to biofuels, food or other products. The properties of thermostability, pH stability, and Ca-independency are important in the development of such fermentation process.ResultsA novel Flavobacteriaceae Sinomicrobium α-amylase (FSA) was identified and characterized from genomic analysis of a novel Flavobacteriaceae species. It is cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
(69 reference statements)
2
19
0
1
Order By: Relevance
“…While the former position is well-conserved as an aromatic one throughout the entire α-amylase family GH13, it is mostly occupied by phenylalanine or tryptophan2324 and the presence of the tyrosine (Figure 2) here in ASKA seems to be unique for the GH13 subfamily11. Because tryptophan is highly characteristic of the GH13 subfamilies 6 and 7, which include plants, archaeons and flavobacteria232425, phenylalanine, which is found in the GH13 subfamilies 15 and 24 (animals) as well as 27, 28, 32 and 36 (various groups of bacteria), was chosen as the substitute for Tyr-187 in the mutant. The latter mutant position in CSR-II, Leu-189, is a conserved position, but if it is replaced then isoleucine (Figure 2) is often found2324.…”
Section: Resultsmentioning
confidence: 98%
“…While the former position is well-conserved as an aromatic one throughout the entire α-amylase family GH13, it is mostly occupied by phenylalanine or tryptophan2324 and the presence of the tyrosine (Figure 2) here in ASKA seems to be unique for the GH13 subfamily11. Because tryptophan is highly characteristic of the GH13 subfamilies 6 and 7, which include plants, archaeons and flavobacteria232425, phenylalanine, which is found in the GH13 subfamilies 15 and 24 (animals) as well as 27, 28, 32 and 36 (various groups of bacteria), was chosen as the substitute for Tyr-187 in the mutant. The latter mutant position in CSR-II, Leu-189, is a conserved position, but if it is replaced then isoleucine (Figure 2) is often found2324.…”
Section: Resultsmentioning
confidence: 98%
“…Engineered FSADSK retained 50% of activity at 100 8C and a 30 min extended half-life at elevated temperatures [12]. Finally, the detailed characterization of another calcium-independent aamylase (Gt-amyII) from G. thermoleovorans revealed that this thermozyme is even capable of hydrolyzing raw starches at industrial sub-gelatinisation conditions [13 ].…”
Section: Current Opinion In Microbiologymentioning
confidence: 98%
“…In contrast to S. oceani SCSIO 03483 T , strain 5DNS001 T was able to hydrolyse pectin and starch in MA and produce novel pectinase and a-amylase (Li et al, 2014).…”
Section: Flavobacterium Limicola St-82 T (Ab075232)mentioning
confidence: 98%